Produksi selada (Lactuca sativa l.) dengan penyinaran lampu led merah dan biru di malam hari pada teknologi hidroponik sistem terapung termodifikasi - Ardiansyah Azhary Suhandoko; Sumarsono Sumarsono; Endang Dwi Purbajanti (Journal of Agro Complex, 2018)
This research has an aim to observe the production of lettuce (Lactuca sativa L.) on hydroponic technology of floating system with red and blue LED (Light Emitting Diode) at night. This research was conducted inside the Screenhouse in which located on the top of Griya Kads House building, Bulusan Village, Tembalang Sub-district from May to June 2017. The research was conducted by 3x3 factorial experiments in Nested Design with 3 replications. The first factor was 0, 1.5 and 3 hours irradiation of red and blue LED lights at night. The second factor was 3, 5 and 7 ml/liter of AB mix nutrient concentration which was nested in the first factor. The data collected were fresh weight, dry weight and root canopy ratio. The results of the study showed that the treatment of AB mix nutrient concentration had no significant effect on all parameters. The production of lettuce with level of 5 ml concentration of AB mix was quite good, yet 3 ml and 7 ml levels didn’t improve lettuce production. The duration of red and blue LED irradiation only resulted in an increase in the production of canopy fresh weight. This research can be concluded that 3 hours was sufficient to give the good results to improve the results of lettuce plants production. Keywords : Lettuce Production, AB Mix Nutrition, Red and Blue LED.